THE RELATIONSHIP BETWEEN NUMERICAL ABILITY, CONFIDENT, AND PARENT’S ATTENTION TO MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS X OF SMA MUHAMMADIYAH 7 YOGYAKARTA - Cempaka Ayu Wardani; Suparyan Suparyan (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Low student learning outcomes associated with many factors. The relationship between numerical skills, confidence, and parents' attention is possibly related to learning outcomes. This research aims to determine the presence or absence of positive and significance the relationship between numerical skills, confidence, and parent's attention with Mathematics Learning Outcomes in Students Class X SMA Muhammdiyah 7 Yogyakarta in even semester in the academic year of 2016/2017. The population in this research was the students of X SMA Muhammdiyah 7 Yogyakarta in 2016/2017, consisting of class  XA, XB, and XD, totaling 87 students. Samples were taken from XA as the research sample class and with the random sampling technique. The writer uses a questionnaire method to collect numerical skills, confidence, parent's attention, and test method to get the resulting learning of math—the research instrument: validity test and reliability test. Test requirement analysis includes a test of normality, a test of linearity, and independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed that there was a positive and significant relationship between numerical skills, confidence, and parent's attention with mathematics learning outcomes in students class X in even semester of SMA Muhammadiyah 7 Yogyakarta in the academic year of 2016/2017. It is showed by Fcount  Ftable is  with  R= 0,8627 and R2 = 0,7442 with , with Relative Contribution(RC) , RC  and RC , Effective Contribution(EC) , EC and EC .